Combatting the global crime of bribery: a report on Canadian foreign official anti-bribery policy. Issue 4 (2nd October 2017) - Leasure, Peter
Abstract : Purpose: The purpose of this paper is to provide an updated review of Canadian foreign official anti-bribery policy. Design/methodology/approach: To achieve this objective, seven factors were examined. Several factors have been emphasized by the Organisation for Economic Co-operation and Development, and others are original. Findings: The results indicate that while Canada is making progress towards strengthening its foreign official anti-bribery policy, significant weaknesses still remain. Originality/value: This study adds to the literature in this area by utilizing several new factors which attempt to gauge the effectiveness of foreign official anti-bribery policy.